(untitled) (Conferencea, 2023)
The hygiene of physical education and sports is the science of the impact of various factors related to physical culture and sports on the health of the athletes: environmental conditions where physical exercises are performed; the content and organization of physical exercises; the volume and intensity of physical exertion during physical training; the nature of food; Sportsman’s technical equipment and outfit. Based on the study of the influence of these factors, I am developing hygienic recommendations, norms and rules.